2019
DOI: 10.3390/catal9121057
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Trend on the Regulation Methods for Nanozyme Activity and Its Application

Abstract: Natural enzymes, such as biocatalysts, are widely used in biosensors, medicine and health, the environmental field, and other fields. However, it is easy for natural enzymes to lose catalytic activity due to their intrinsic shortcomings including a high purification cost, insufficient stability, and difficulties of recycling, which limit their practical applications. The unexpected discovery of the Fe3O4 nanozyme in 2007 has given rise to tremendous efforts for developing natural enzyme substitutes. Nanozymes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 99 publications
(85 reference statements)
0
22
0
Order By: Relevance
“…Generally, to make the nanozymes have higher catalytic activity, three regulation strategies using different thoughts can be employed to promote the binding of nanozymes to substrates by (i) increasing their surface area/volume ratio, (ii) reducing the size of nanozymes, (iii) promoting the preferential exposure of active atoms with catalytic activity, and (iv) increasing the number of suspended bonds. 67,90 The core goal of these regulation strategies is to improve the exposure degree of the nanozyme active site and its similarity with the structure of active site of natural enzymes. We then describe the tunable enzyme-like activity, stability, and multifunctionality of Mo-based nanozymes based on the physicochemical property (size, morphology, doping, multicomponent synergistic effect, and surface modification)-related structurefunction relationship.…”
Section: Unique Properties Of Mo-based Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, to make the nanozymes have higher catalytic activity, three regulation strategies using different thoughts can be employed to promote the binding of nanozymes to substrates by (i) increasing their surface area/volume ratio, (ii) reducing the size of nanozymes, (iii) promoting the preferential exposure of active atoms with catalytic activity, and (iv) increasing the number of suspended bonds. 67,90 The core goal of these regulation strategies is to improve the exposure degree of the nanozyme active site and its similarity with the structure of active site of natural enzymes. We then describe the tunable enzyme-like activity, stability, and multifunctionality of Mo-based nanozymes based on the physicochemical property (size, morphology, doping, multicomponent synergistic effect, and surface modification)-related structurefunction relationship.…”
Section: Unique Properties Of Mo-based Nanozymesmentioning
confidence: 99%
“…Second, the shape and morphology of nanozymes play important roles in regulating their catalytic activity. 90 For example, MoO 3−x nanourchins (NUs) possessed OXD-like activity to produce O 2 •-, whereas MoO 3−x NSs could not produce measurable levels of ROS (Figures 7A and 7B). 39 In another study, Liu et al reported that MoO 3 nanorods exhibited higher POD-like activity than MoS 2 NSs and MoO 3 nanowires.…”
Section: Size and Morphologymentioning
confidence: 99%
“…Secondly, with the involvement of CHO, the production of H 2 O 2 is inevitable, so nanozymes with only peroxidase-like activity are ideally suitable. Undoubtedly, these rules pose some challenges to such a ChE-CHO-nanozyme system: on the one hand, due to the inherent fragile nature of bioenzymes, a mild detection environment is still necessary for these assays; on the other hand, many nanozymes often show multiple enzyme activities [66,67]. It is difficult to achieve a nanozyme that only presents peroxidase-mimicking activity [68], and such that interference originating from other enzyme-like activities may exist during the detection process.…”
Section: Ternary Che-cho-nanozyme Assaysmentioning
confidence: 99%
“…Since colorimetric detection of bio-molecules is based on electronic transfer processes and co-related with substrate surface area, porosity, and heteroatom in the lattice. [38][39][40] Since porous 2D carbon bears a vast surface area and unique electronic structures; therefore, it can play an exciting role for the artificial enzyme. Presently, bio-waste derived 2D carbon nanomaterials are acquiring much more attention in various recommended technological projects 41,42 , e.g., supercapacitor [43][44][45] , batteries 46 , and adsorbents 47 , etc.…”
Section: Introductionmentioning
confidence: 99%